Ballistic performance and statistical evaluation of multilayered armor with epoxy-fique fabric composites using the Weibull analysis (2019)
The ballistic performance of multilayered armor system (MAS) with front ceramic tile, followed by a laminate of up to 50 vol.% of fique fabric-reinforced epoxy matrix and back by a 5062H34 aluminum alloy was evaluated. The backface signature (BFS) caused by the bullet in a block of clay witness behind the target was used to evaluate the MAS ballistic performance according to international standards. The results using high-velocity 7.62mm ammunition show a BFS similar to a MAS second layers of KevlarTM laminate with the same thickness. The Weibull analysis statistically provides the reliability of BFS test results. Fracture examinations by scanning electron microscopy (SEM) revealed that the epoxy-fique fabric composite has different types of energy dissipation mechanisms. These are the same capture of ceramic fragments by a mechanic of incrustation presented in KevlarTM laminate. Among the tested materials, the 40 vol.% fabric composite was found to be a better alternative to replace KevlarTM. The lower cost of the epoxy-fique fabric composite is an additional advantage that favors its substitution for the aramid fabric.